T2 phase site occupancies in the Cr–Si–B system: a combined synchroton-XRD/first-principles study. (1st July 2021) - Dorini, Thiago T.; Freitas, Bruno X. de; Ferreira, Pedro P.; Chaia, Nabil; Suzuki, Paulo A.; Joubert, Jean-Marc; Nunes, Carlos A.; Coelho, Gilberto C.; Eleno, Luiz T.F.
Graphical abstract: Abstract: Boron and Silicon site occupancies of the T2 phase in the Cr–Si–B system were investigated experimentally and by first-principles electronic-structure calculations. A sample with nominal composition Cr 0.625 B 0.175 Si 0.2 was arc-melted under argon, encapsulated in a quartz-tube and heat-treated at 1400 ∘ C for 96 hours. It was then analyzed using Scanning Electron Microscopy (SEM) and X-Ray Diffractometry (XRD) with synchrotron radiation. An excellent agreement was obtained between experiments and theoretical calculations, revealing that Si occupies preferably the 4 a sublattice of the structure, as boron atoms in 8 h nearest-neighbors form very stable dumbbell bonds. Site preferences are thus a key factor for the stabilization of the structure. The results of this work provide important information to support a better description of this phase in alloys with Si and B, since T2 phases are known to occur in many important Transition Metal–Si–B ternary systems, such as Nb/Mo/W/Ta/V–Si–B.